Concerning the theory of operator averages - Arlinsky, Yu. М. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
New properties of operator connections and means are established. Specifically, representations of an arbitrary connection by means of a concave representing function, an estimate of the norm of a connection in a von Neumann-Schatten ideal, a relation between operator means and convolutions onto operator domains are obtained.